The believer's call to commitment - Murray, Andrew, 1828-1917.; Murray, Andrew, 1828-1917. (Minneapolis, Minn. : Bethany House, 2005)
"Newly updated for today's reader, this devotional study of Ephesians explores how a committed Christian life begins with dependence on the Holy Spirit"--Provided by publisher.
Our devotional life and commitment -- Commitment : the New Testament standard -- Commitment : the great need of the church -- Commitment and the spiritual life -- The seal of the Spirit -- The Spirit of wisdom -- The Spirit of access -- The temple of the Spirit -- The Spirit of missions -- The Spirit of power -- The unity of the Spirit -- The Spirit of unity -- Grieving the Spirit -- Being filled with the Spirit -- The sword of the Spirit -- The Spirit of prayer -- Ephesians in review -- Because of unbelief -- All things are possible with God -- To Him be glory.
First published in 1909 as Aids to devotion.
"A devotional study of Ephisians presented for today's reader"--Cover.
College Students
Keywords: Spiritual life -- Christianity